Gandong River Overflow Flood Disaster Risk Analysis (Case Study: Sukorejo Village, Bojonegoro Subdistrict, Bojonegoro Regency) - Sandoko*, Anam; Sholahuddin, Moh; Nevila Rodhi, Nova (Riwayat: Educational Journal of History and Humanities, 2024)
Bojonegoro Regency is one of the areas in East Java that has lowlands and frequent floods. Recorded in Bojonegoro Regency BPBD data in 2022 there have been 7 flood disasters. The average flood occurs due to the inability of the river to accommodate the increasing volume of water due to high rainfall. So the higher the rainfall, the higher the risk of flooding. In this study, a risk analysis of flood disasters due to river overflows was conducted. The parameters used are threats, vulnerability (physical, economic, social and environmental), and government capacity. The research method used was qualitative. This research was conducted in Sukorejo Village. The results obtained were that the threat of the Gandong River overflow flood in Sukorejo Village was classified as low with a water level of 700 cm, the vulnerability of the Gandong River overflow flood disaster was in the low category, and the capacity of the Gandong River overflow flood disaster was also low, causing a high level of disaster occurrence, and the risk of the Gandong River overflow flood disaster in Sukorejo Village fell into the low category.